2021
DOI: 10.3390/met11040657
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal Kinetic Degradation of Hybrid CNT/Alumina Epoxy Nanocomposites

Abstract: Due to the synergistic effect that occurs between CNTs and alumina, CNT/alumina hybrid-filled epoxy nanocomposites show significant enhancements in tensile properties, flexural properties, and thermal conductivity. This study is an extension of previously reported investigations into CNT/alumina epoxy nanocomposites. A series of epoxy composites with different CNT/alumina loadings were investigated with regard to their thermal-degradation kinetics and lifetime prediction. The thermal-degradation parameters wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In order to estimate the relative effect of fillers, Flame retardancy index (FRI) is used. [ 25 ] This parameter is a dimension less quantity and offers a fair estimation of the flame retarding capability of the composite. It is given by the equation: FRI=THR×pHRRTTINeat polymerTHR×pHRRTTIComposite …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to estimate the relative effect of fillers, Flame retardancy index (FRI) is used. [ 25 ] This parameter is a dimension less quantity and offers a fair estimation of the flame retarding capability of the composite. It is given by the equation: FRI=THR×pHRRTTINeat polymerTHR×pHRRTTIComposite …”
Section: Resultsmentioning
confidence: 99%
“…The large contact area of GNP and the bridging of GNP by MWCNT are reported to be responsible for synergy in electrical conduction, for a filler ratio of 1 (MWCNT):9 (GNP). Some investigators [ 11 ] have reported synergy between aluminum trihydrate (ATH) and MWCNT in improving the thermal stability of epoxy composites. It is reported that higher loading of the hybrid fillers results in higher char residue and improved thermal stability of the epoxy composite.…”
Section: Introductionmentioning
confidence: 99%